User embracement and care for people with disabilities in the Family Health Strategy: perception of the health team - Gonçalves, Luana Stefanie Silvino; Fumagalli, Igor Henrique Teixeira; Lago, Luana Pinho de Mesquita; Junior, Wilson Mestriner (O Mundo da Saúde, 2024)
In Brazil, there are more than 12 million people with disabilities who are covered by primary health care, which plays an important role in promoting access, reception, and care for this population. The study aims to analyze the perceptions of a family health team regarding the embracement and care of people with disabilities. A cross-sectional mixed methods study was carried out, with an online questionnaire and interviews with 16 professionals from a family health unit. We observed a strong understanding among the professionals regarding the importance of the subject, and one of the potentialities lies in the user embracement that sustains the relationship with the health team in an integral, longitudinal and humanized way. Difficulties in carrying out health promotion actions and the lack of infrastructure meeting minimum accessibility requirements were the biggest barriers mentioned, which, together with communication barriers and lack of knowledge about the subject, create an unfavorable environment for health care. It is possible to indicate qualification of the professional team, which suggests that health managers allow continuing education, and that the professionals take continuing education as an opportunity to reflect on the work process and to transform their practices.